Modernisasi Penggunaan Papan Tulis Interkatif (PTI) Di SMP Negeri 3 Tanjung Beringin - Nandani, Fitri; Widia, Widia (EL-EMIR INSTITUTE, 2024)
Modernization is the latest update. Like interactive whiteboards, initially the world of education used blackboards during the learning process, but with the increasingly rapid advances in technology nowadays, blackboards have also turned into interactive whiteboards. The world of education does not want to be left behind by existing technological advances, the world of education will go hand in hand with the progress of technological development and growth at this time. SMP Negeri 3 Tanjung Beringin is one of the schools that provides technological facilities in the form of interactive whiteboards and projectors. The school will keep up with current developments. The approach used from the results of the process in using this interactive whiteboard is the observation method with a descriptive pattern approach by conducting observations and interviews with the school and students. So the method used in this approach is very appropriate. The results of the observations are that the SMP Negeri 3 Tanjung Beringin school has two interactive screen units and has 4 projectors which can be used as learning media in the classroom. Using an interactive whiteboard can help increase students' motivation and interest in the learning process.